EXCLI Journal; 21:Doc580; ISSN 1611-2156 2022
DOI: 10.17179/excli2022-4702
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of hematological parameters in rheumatoid arthritis patients receiving biological therapy: contribution to prevention of avoidable hematological complications

Jana Pereckova,
Silvia Martiniakova,
Juraj Payer
et al.

Abstract: Administration of biological therapy (BT) in rheumatoid arthritis (RA) patients is often associated with hematological complications, which result in switching among therapies. Thus, there is an instant need for suitable screening parameters that will help to individualize the therapy and minimize the onset of adverse effects. We analyzed the hematological profile of 99 RA patients receiving TNFα (Adalimumab - ADA, Golimumab - GOL, Etanercept - ETA) or IL-6 receptor (Tocilizumab - TCZ) inhibitors in order to f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 41 publications
0
1
0
Order By: Relevance
“…Pereckova showed that RA patients treated with csDMAR have higher NLRs and PLRs compared to healthy donors and patients receiving anti-TNF and anti-IL6. However, the NLRs and PLRs of patients receiving anti-TNF and anti-IL6 are comparable [17]. The effect of treatment duration on these indices was not discussed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pereckova showed that RA patients treated with csDMAR have higher NLRs and PLRs compared to healthy donors and patients receiving anti-TNF and anti-IL6. However, the NLRs and PLRs of patients receiving anti-TNF and anti-IL6 are comparable [17]. The effect of treatment duration on these indices was not discussed.…”
Section: Introductionmentioning
confidence: 99%
“…In the realm of novel treatments for rheumatoid arthritis, specifically those involving anti-CD20 and JAK inhibitors (JAKis), it is important to note their substantial impacts on lymphocyte and neutrophil counts, as evidenced by previous research [15,16]. However, the influence of these treatments on hematological indices remains an area of limited investigation [17][18][19]. Pereckova showed that RA patients treated with csDMAR have higher NLRs and PLRs compared to healthy donors and patients receiving anti-TNF and anti-IL6.…”
Section: Introductionmentioning
confidence: 99%
“…Autoimmune diseases are immune-mediated disorders affecting joints, kidneys, and others that usually alternate activity with quiescent stages [ 1 ]. These inflammatory disorders are characterised by, increased production of proinflammatory cytokines [ 2 ]. Which include tumor necrosis factor alpha (TNFα), interleukin-17 (IL-17), and interleukin (IL-6) [ 3 ].…”
Section: Introductionmentioning
confidence: 99%